Foundations for fairness in digital health apps - Buda, Teodora Sandra; Guerreiro, João; Omana Iglesias, Jesus; Castillo, Carlos; Smith, Oliver; Matic, Aleksandar (Frontiers in Digital Health, 2022)
Digital mental health applications promised scalable and cost-effective solutions to mitigate the gap between the demand and supply of mental healthcare services. However, very little attention is paid on differential impact and potential discrimination in digital mental health services with respect to different user groups (e.g., race, age, gender, ethnicity, socio-economic status) as the extant literature as well as the market lack the corresponding evidence. In this paper, we outline a 7-step model to assess algorithmic discrimination in digital mental health services, focusing on algorithmic bias assessment and differential impact. We conduct a pilot analysis with 375 users by way of a case-study of the model applied on a digital wellbeing service called Foundations that incorporates a rich set of 150 proposed activities. We further apply the 7-step model on the evaluation of two algorithms that could extend the current service: monitoring step up model, and a popularity-based activities recommender system. This manuscript applies an algorithmic fairness analysis framework for digital mental health and explores differences in the outcome metrics for the interventions, monitoring model, and recommender engine for the users of different age, gender, type of work, country of residence, employment status and monthly income.